(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper provides a comprehensive overview of the criteria used to test and standardize medicinal plants and components in the pharmaceutical sector. Natural or herbal therapies are becoming increasingly popular as alternatives to commercially produced drugs due to their low risk of side effects. As herbal therapeutic items become more popular, concerns regarding their effectiveness, safety, and quality arise. These problems stem from the lack of herbal therapy standardization criteria. To maintain quality, herbal medicinal plant components must be standardized using rigorous standards and analytical methods. Herbal treatments are tested and standardized using several physical, chemical, and biological approaches. These methods determine if herbal plant materials and formulations are safe, pure, and effective and constitute the basis of quality control. Analytical methods like TLC, HPTLC, GC, LC-MS, UPLC, UHPLC, UPLC-MS, and UHPLC-MS are used to quantify herbal drugs and their formulations. This assessment emphasizes these methods. Standardized assessment criteria are necessary to guarantee herbal medical product active ingredients are dependable and effective. These analytical methods can standardize and test herbal medicines. This preserves herbal medicine quality and reliability. If these guidelines are followed, herbal medicines will meet safety, efficacy, and consistency criteria.